The palliative effects of folic acid on retinal microvessels in diabetic retinopathy via regulating the metabolism of DNA methylation and hydroxymethylation. Issue 2 (20th December 2021) - Liu, Xianli; Cui, Hongbao
ABSTRACT: Diabetic retinopathy (DR) is one of the severe microvascular complications of diabetes. The protective effects of FA on retinal vascular endothelial cells against high glucose levels involve in multiple aspects in DR; however, the underlying mechanism is not fully elucidated. In present study, we investigated the transcriptome as well as genome-wide DNA methylation and hydroxymethylation signature in human retinal microvascular endothelial ACBRI 181 cells cultured within high glucose (HG) medium supplemented with or without FA by RNA-seq, MeDIP-seq, and hMeDIP-seq. Total 3308 differential expressed genes (DEGs) were involved in multiple biological processes and molecular functions containing angiogenesis, inflammation, S-adenosyl methionine metabolism, and hypoxia response. Moreover, the global DNA methylation and hydroxymethylation in ACBRI 181 cells with FA treatment were both compromised compared to HG. Combined with transcriptome data, four subclusters of DEGs with hyper- or hypomethylated promoters were further verified. Unexpectedly, promoters of these 487 genes all displayed a pattern of increased DNA hydroxymethylation. Furthermore, hyperglycemia rat model was established and administered with FA. The DNA methylation and hydroxymethylation changes of selected target genes COL1A1, ITGA7, MMP-14, and VEGFB confirmed by MeDIP-qPCR were consistent with the results in human ACBRI 181 cells. Finally, the presence of activated DNMT1 and TET2 induced by FA was determined in ACBRI 181 cells and hyperglycemia rat. Taken together, this research provided a resource of expression and epigenetic profiles in retinal microvascular endothelial cell, emphasizing a pharmacological mechanism of FA on DNA methylation and hydroxymethylation regulation in retinal microvessel cells of DR.